Degranulation of Human Platelets by the Thrombin Receptor Peptide SFLLRN: Comparison with Degranulation by Thrombin - Kinlough-Rathbone, R L; Perry, D W; Guccione, M A; Rand, M L; Packham, M A (Thrombosis and Haemostasis, 1993)
A new, simplified method of degranulating human platelets using the thrombin receptor peptide SFLLRN (20 |iM) is described; released fibrinogen cannot be converted to fibrin, and the platelets are not exposed to a proteolytic enzyme, as they are when thrombin is used for degranulation. The peptide-degranulated platelets regain their disc shape and are recovered as single platelets which have released approximately 90% of the contents of their dense granules. Their procoagulant activity is greater than that of control platelets, but somewhat less than that of thrombin-degranulated platelets. Without added fibrinogen, the peptide-degranulated platelets aggregate slightly in response to 50 μM SFLLRN, and to collagen, arachidonic acid, the thromboxane A2 mimetic U46619, platelet activating factor, ADP, and the divalent cation ionophore A23187; added fibrinogen enhances aggregation caused by these agonists. Extensive aggregation of peptide-degranulated platelets is caused by thrombin in the absence of added fibrinogen; it may be that the alternative thrombin receptor that is not activated by SFLLRN is responsible for the strong response to thrombin. Aggregation responses to most of the agonists are greater than those observed previously (10) with thrombin-degranulated platelets. By this method, platelets are obtained that have been degranulated in a way that is similar to in vivo degranulation. They are useful for studies of platelet responses without the complicating effects of released granule contents, and for investigation of the characteristics and functions of platelets that have come in contract with release-inducing agents in vivo.